The Border as a Tourist Resource. Possibilities of Bajo/Baixo Guadiana - Jurado-Almonte, Jose Manuel; Pazos-García, Francisco José (Revista de Estudios Andaluces, 2018)
In the area of integration of the European Union the borders still persist, now without the difficulties and barriers of yesteryear, but maintaining numerous symbols and elements of the cultural heritage that continue to make a difference. They are “dividing lines” and, at the same time, strips of transitional territories with an important natural and cultural heritage that now become attractive resources for novel tourist demands. Therefore, border tourism is already being studied as a new product where the border and history resource is the main attraction and destination, although in a complementary way to other tourism resources and products. Apart from other territories and border destinations in Europe or the world, our research concern focuses on the Luso-Spanish border, the “Raya” or “Raia”, at its southern end, in the Lower Guadiana, in spaces that participate in the Algarve, Baixo Alentejo and Huelva. In this territory are combined tourist destinations (Algarve and West Coast of Huelva) with a very close interior and unknown to most tourists staying on that coastal edge, just a few tens of kilometers. However, in recent years, an incipient tourist space seems to open up inland (and waters) from the coast. The Guadiana estuary acts as a gateway to an interior rich in resources and historical-artistic and natural heritage and that could benefit from border tourism. Our main hypothesis is that the development of border tourism could be an opportunity for this transboundary territory. In this work we are dealing, therefore, with: - Analyze the geographical, natural and cultural heritage of this cross-border area, with a brief profile of its population and cooperation policies on accessibility and tourism infrastructures. - diagnose this novel tourist product for this particular territory, - and make proposals capable of promoting this tourist activity.